Value at Risk (VaR) and Expected Shortfall (ES) Measurements for Foreign Currency Portfolio Using EWMA and GARCH (1,1) - Firly Armanda; Fatwa Aulia; Jodi Surya Gustanto; Jalil Mujib Tan Ismail; Jonatan Halomoan; Dianita Fitriani Pogram; Girindra Chandra Alam; Dewi Hanggraeni (Syntax Corporation, 2022)
This study assesses the Value at Risk (VaR) and Expected Shortfall (ES) methods in gauging exchange rate risk in PT Telkom Indonesia Tbk, using historical Bank Indonesia closing rates USD/IDR and JPY/IDR from January 2022 - December 2022. Results demonstrate that the ES calculation with Confidence Level (CL) 99%, using the Exponentially Weighted Moving Average (EWMA) and Generalized Autoregressive Conditional Heteroskedasticity (1,1) (GARCH (1,1)) models, provides conservative measures for USD and JPY exposures. These measures, reflecting the highest potential losses, are consistent with management's cautious approach towards currency exchange market risk. Furthermore, based on the ES calculations in this study, it is suggested that PT Telkom Indonesia retains a minimum deposit of 30,000,000,000 IDR, equivalent to roughly 1.007% of its short-term liabilities, which is substantially below the stipulated 25% minimum deposit to efficiently navigate potential foreign exchange risks.